SOPAPEI BEACH TOURISM DEVELOPMENT STRATEGY IN SULI VILLAGE, CENTRAL MALUKU DISTRICT - Meitha Monita Kaihatu; Lilian Sarah Hiariey (Yayasan Education and Social Center, 2023)
Sopapei Beach has the potential to be developed and plays a role in increasing community and regional income. The potential of the Sopapei Beach tourism object still needs to be developed again to become the most popular tourist destination in Suli Village, Central Maluku Regency. A strategy is a form of effort made to create and preserve the Sopapei Beach tourist area so that it can be more competitive in attracting tourists. This study aimed to determine the development strategy used by the Sopapei Beach tourism object and the alternative strategies used per the conditions of the Sopapei Beach tourism object. The analysis used is a SWOT analysis, which is an analysis that is intended to see the extent to which the implementation of tourism object development strategies in increasing tourists is based on strengths, weaknesses, opportunities, and threats. The study results obtained that the development strategy used by Sopapei beach managers was the strategic focus or a combination of cost leadership. And differentiation to develop Sopapei Beach, managers paid attention to tourists and tourism products on Sopapei Beach to increase the number of tourists visiting. In contrast, the alternative development according to the situation at the Sopapei Beach tourist attraction based on SWOT analysis is the potential for Sopapei Beach tourism objects which include beautiful and excellent and pristine natural panoramas, abundant water sources, and a comfortable tourist atmosphere. So owners and managers must increase cooperation with the local government of Central Maluku Regency, especially the tourism office.We are improving existing tourism products and tourist attractions such as facilities and infrastructure, security, and services, and organizing festivals to improve the quality and quantity of Sopapei Beach.